1980
DOI: 10.7326/0003-4819-92-2-301
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Autonomic Neuropathy in Diabetes Mellitus

Abstract: Pathologic changes in the autonomic nervous system were studied postmortem in five cases of insulin-dependent diabetes of early onset. All had had clinical evidence of peripheral sensorimotor neuropathy and developed disturbances of autonomic function that included postural hypotension, diarrhoea, bladder dysfunction, impotence (in the men), and signs of cardiac denervation. In coeliac and other sympathetic ganglia there were many distended ('giant') or vacuolated neurons as well as enlarged club-shaped neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
0
7

Year Published

1984
1984
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(133 citation statements)
references
References 6 publications
10
116
0
7
Order By: Relevance
“…In human type I diabetes 30 and in STZ-diabetic rats, there are reports of the presence of giant axons, and of the presence of aggregates of intra-axonal subcellular organelles. [31][32][33] There are also observations of some regenerative activity in diabetic nerves. [34][35][36] Becker et al (2000) 6 compared the concentrations of NA and adrenaline in cavernous and systemic blood during penile erection in humans, and found a significant reduction of NA in cavernous blood, while adrenaline levels rose in peripheral and cavernous blood during developing erection.…”
Section: Discussionmentioning
confidence: 92%
“…In human type I diabetes 30 and in STZ-diabetic rats, there are reports of the presence of giant axons, and of the presence of aggregates of intra-axonal subcellular organelles. [31][32][33] There are also observations of some regenerative activity in diabetic nerves. [34][35][36] Becker et al (2000) 6 compared the concentrations of NA and adrenaline in cavernous and systemic blood during penile erection in humans, and found a significant reduction of NA in cavernous blood, while adrenaline levels rose in peripheral and cavernous blood during developing erection.…”
Section: Discussionmentioning
confidence: 92%
“…Autonomic neuropathy is a severe and crippling complication of T1D of long duration; recent evidences indicate that immune pathogenesis plays an important role in this complication [12][13][14][15]. Lymphocytes and plasma cells infi-ltrate autonomic ganglia and nerve bundles [13], and in the circulation, activated T-cells [14] and complement breakdown products [15] are present at elevated levels.…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytes and plasma cells infi-ltrate autonomic ganglia and nerve bundles [13], and in the circulation, activated T-cells [14] and complement breakdown products [15] are present at elevated levels. It is well reported that autoantibodies to nervous tissues were found in T1D neuropathic patients, but not in patients with T1D of similar duration but without complications [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The gastrointestinal system is one of the commonly affected systems where the vagus nerve usually shows signs of demyelination [1][2][3] and degeneration of myelinated fibres, axonal terminals and dendrites [2][3][4][5][6]. Gastric dysfunctions (diabetic gastropathies) associated with diabetic vagal lesion range from, tachygastria, antral hypomotility, and frank gastroparesis to abnormal myoelectric activities.…”
Section: Introductionmentioning
confidence: 99%